IMPACT OF VIRTUAL LEARNING ON CHEMISTRY STUDENTS’ ACADEMIC PERFORMANCE IN DISTANCE LEARNING INSTITUTE, UNIVERSITY OF LAGOS, NIGERIA - Adesoji, Adedoyin Oluseyi; Ajadib, Titilayo Adeoye (FUDMA Journal of Sciences, 2026)
In recent times, the growing popularity of virtual learning in higher institutions has been observed, however, there is a limited research on the effect of distance learning institutions, especially Chemistry, on students’ academic performance. Chemistry is viewed as an abstract and a difficult course by many students; hence, this study examined the effects of virtual learning on the academic performance of Chemistry students in Distance Learning Institute (DLI), University of Lagos. Virtual Learning and Academic Performance Questionnaire was distributed via stratified random sampling technique. Descriptive statistics was used in analyzing the data related to the research questions while inferential statistics used in testing the hypotheses was Chi-square. The findings showed that the physical facilities in terms of structures and computers were adequate for Chemistry students, revealing a significant effect of virtual learning on academic performances of learners of Chemistry Education of the Distance Learning Institute. The study indicated that there is better access and use of virtual tools with better academic performance in DLI, at 0.05 significant level, leading to a positive relationship between engagement in virtual activities and Chemistry performance. The internet quality, timely academic support, and interactive virtual sessions significantly affect students’ virtual learning experience. Based on these findings, it is recommended that government and school management should improve the internet infrastructure, provide adequate learning materials, adopt multiple learning platforms, provide better e-learning environment for facilitators, provide better student support services and ultimately integrate interactive and gamified tools in higher Institutions.
Keywords: Academic performance; Chemistry; Distance learning; Students; Virtual learning